Book Review: Juxtaposition of K.H. Ahmad Dahlan and John Dewey’s Progressive Thoughts - Mu’arif Mu’arif (Universitas Muhammadiyah Surakarta, 2017)
Book title : Paradigma Pendidikan Berkemajuan: Teori dan Praksis Pendidikan Progresif Religius KH Ahmad Dahlan Author : Dr. Mohamad Ali, M.Pd. Pages : xxxvi + 326 pages Edition : I, October 2017 Publisher : Suara Muhammadiyah